Identification of Smac mimetics as novel substrates for p-glycoprotein. (January 2019) - Hugle, Manuela; Czaplinski, Sebastian; Habermann, Karoline; Vogler, Meike; Fulda, Simone
Abstract: Multidrug resistance (MDR) in cancer patients undergoing chemotherapy is preventing effective treatment of multiple cancer types including pediatric tumors. Resistance to chemotherapeutic drugs in cancer cells is frequently associated with high expression of p-glycoprotein, a transporter in the plasma membrane that can mediate cellular drug export. Here, we generated pediatric cancer cells with acquired resistance to the chemotherapeutic drug vincristine (VCR). In these cells, acquired resistance is associated with increased expression of p-glycoprotein. VCR-resistant cells display an MDR phenotype and have acquired resistance to multiple other chemotherapeutic drugs including doxorubicin (DOXO) and etoposide (ETO). Notably, we discovered that these cells also display cross-resistance with several Smac mimetics, a novel class of experimental cancer therapeutics designed to induce apoptosis by inhibiting Inhibitor of Apoptosis (IAP) proteins. Resistance to Smac mimetics is reversible in the presence of p-glycoprotein inhibitors, highlighting Smac mimetics as novel substrates for p-glycoprotein. The identification of Smac mimetics as substrates for p-glycoproteins may influence the design of future clinical trials to prevent usage of Smac mimetics in the context of MDR or, alternatively, combine Smac mimetics with p-glycoprotein inhibitors to maximize their efficiency. Graphical abstract: Highlights: Cancer cells with acquired resistance to VCR overexpress p-glycoprotein. VCR-resistant cancer cells are cross-resistant with several chemotherapeutics. VCR-resistant cancer cells display cross-resistance with Smac mimetics. P-glycoprotein inhibitors restore sensitivity to Smac mimetic-induced apoptosis.